Pengaruh Pengungkapan Sistem Pengendalian Internal terhadap Nilai Perusahaan dengan Agency Cost Sebagai Mediator - Miranda Ariani; Weli Weli (Universitas Pamulang, 2022)
This study aims to analyze the effect of internal control disclosure on firm value and Agency Cost as a mediator. The measurement of the internal control disclosure variable follows the standard guidelines for the internal control system of commercial banks issued by the Financial Services Authority (Number 35/SEOJK.03/2017) and Bank Indonesia (Lamp. SE No. 5/22/DPNP dated September 29, 2003) which consists of of 15 criteria. Firm value is measured by Tobin's Q while agency cost is measured by management ownership. The data analysis method is descriptive statistical analysis and hypothesis testing using path analysis with PROCESS, on SPSS Version 25. The population of this study is all banking companies listed on the Indonesia Stock Exchange in 2016-2019. Based on the research criteria that have been determined, there are 18 banking companies with 59 sample data. The results of hypothesis testing indicate that the internal control disclosure variables and agency costs have an effect on firm value. However, the research results do not provide empirical support for the mediating effect of agency costs. The practical implication of this research is that banking companies can maintain good internal control system disclosure practices in order to maintain a response from the market. Transparency of information is needed by the market so that it contributes to increasing the value of the company.